Battery cell seal, seal assembly for a battery cell, and battery cell with bridging grommet - Patent application
Patent Information
- Application Number
- JP2024547335
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-09
- Filing Date
- 2023-03-07
- Publication Date
- 2025-03-26
Smart Images

Figure 2025508370000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to battery cells, and more particularly to a battery cell including a seal for the battery cell, a seal assembly for the battery cell, and a bridging grommet. [Background technology]
[0002] Consumer electronic devices have certain power requirements. Typically, consumer electronic devices receive power from one or more battery cells (contained within the device itself) or from an external portable battery pack that may contain one or more battery cells. For example, they may use one or more single-use battery cells (commonly referred to as "primary batteries") or one or more rechargeable battery cells (commonly referred to as "secondary batteries") that can be replaced in the device as needed. Battery cells generate electricity by reduction of the cathode and oxidation of the anode. An electrolyte is included to facilitate the movement of ions from the anode to the cathode to balance the flow of electrons.
[0003] Alkaline battery cells (including rechargeable alkaline battery cells) are known to be prone to leakage of alkaline electrolyte from the battery seals. See, for example, Hull et al., “Why Alkaline Cells Leak,” J. Electrochem. Soc., 124(3):332-339, (1977) and Davis et al., “Aspects of Alkaline Cell Leakage,” J. Electrochem. Soc., 125(12):1918-123, (1978). Evidence of alkaline electrolyte leakage can be visually detected when a white powder builds up around the seals of the battery cells. Alkaline electrolyte leakage can be due to creep of the alkaline electrolyte along the negatively polarized electrodes. Alkaline electrolyte leakage can be exacerbated by physical factors such as scratches or other physical deformations / defects in the seals and / or current collectors of the battery cells. Powdered alkaline electrolyte is generally safe for human contact, but contact should be minimized as respiratory, eye, and skin irritation can occur. Furthermore, loss of electrolyte can degrade the performance of the battery cell.
[0004] Polymeric materials, specifically flexible materials such as nylon and various rubbers, are commonly used to manufacture seals for battery cells. However, seals made from such materials can deteriorate over time, causing material failure and increased electrolyte creep within the cell. Thus, it is known that battery cells are prone to electrolyte leakage, for example, due to electrolyte creep, especially along the body of the anode current collector (which is commonly provided in the form of a nail). Of course, other physical phenomena can also cause electrolyte leakage. Previous attempts to prevent leakage of seal assemblies have been made by providing a sealant around the current collector to provide an additional sealing surface in front of the seal itself. However, existing seal assemblies are not effective enough to prevent electrolyte creep, mainly due to material failure of the seal itself, which may be introduced during battery cell manufacturing / assembly and / or may be caused and / or worsened over time. Summary of the Invention
[0005] According to one embodiment, a seal assembly for a battery cell includes a bridge grommet having an opening, a current collector having a head and a stem extending from the head is disposed within the opening, the stem and the bridge grommet forming an interference fit with the opening, the bridge grommet including a cross-linked polymer.
[0006] In a further embodiment, a seal assembly for a battery cell includes an irradiated cross-linked grommet having an opening, a current collector having a head and a stem extending from the head is disposed in the opening, the stem and the irradiated cross-linked grommet form an interference fit with the opening, the irradiated cross-linked grommet includes a radiation-induced cross-linked polymer.
[0007] According to another embodiment, a battery cell includes a housing including a first cover at a first housing end and a second cover at a second housing end. An anode and a cathode are disposed within the housing. A seal assembly is disposed proximate to the first cover, the seal assembly including a current collector having a head and a stem extending from the head, and a bridge grommet having an opening. The stem extends through the opening and forms an interference fit with the bridge grommet. The bridge grommet includes a cross-linked polymer.
[0008] According to another embodiment, a battery cell includes a housing including a first cover at a first housing end and a second cover at a second housing end. An anode and a cathode are disposed within the housing. A seal assembly is disposed proximate to the first cover, the seal assembly including a current collector having a head and a stem extending from the head, and an irradiated cross-linked grommet having an opening. The stem extends through the opening and forms an interference fit with the irradiated cross-linked grommet. The irradiated cross-linked grommet includes a radiation-induced cross-linked polymer.
[0009] According to another embodiment, a method of manufacturing a battery cell including a cross-linked grommet includes providing a pre-formed grommet including a precursor polymer material, cross-linking the precursor polymer material to form a cross-linked grommet including a cross-linked polymer, and incorporating the cross-linked grommet into a battery cell.
[0010] According to another embodiment, a method of manufacturing a battery cell having an irradiated grommet includes providing a preformed grommet comprising a precursor polymer material, irradiating the precursor polymer material to form an irradiated cross-linked grommet comprising a radiation-induced cross-linked polymer, and incorporating the irradiated cross-linked grommet into a battery cell.
[0011] According to another embodiment, a bridge grommet for a battery cell includes an annular polymer disk having a peripheral wall and a central boss surrounding a central opening for receiving a current collector, the polymer material of the annular polymer disk being crosslinked.
[0012] According to another embodiment, an irradiated cross-linked grommet for a battery cell includes an annular polymer disk having a peripheral wall and a central boss surrounding a central opening for receiving a current collector, the annular polymer disk including a radiation-induced cross-linked polymer.
[0013] In yet another embodiment, a battery cell includes a housing including a first cover at a first housing end and a second cover at a second housing end, an anode and a cathode disposed within the housing, and a bridge grommet adjacent the first cover, the bridge grommet including a cross-linked polymer.
[0014] In a further embodiment, a battery cell includes a housing including a first cover at a first housing end and a second cover at a second housing end, an anode and a cathode disposed within the housing, and an irradiated crosslinked grommet proximate to the first cover, the irradiated crosslinked grommet including a radiation-induced crosslinked polymer.
[0015] The above-described embodiments of the bridging grommet for a battery cell, the irradiated grommet for a battery cell, the seal assembly, the battery cell, and / or the method of forming a battery cell may further include any one or more of the following optional features, structures, and / or configurations.
[0016] In all embodiments, the crosslinked grommet comprises a crosslinked polymer. Similarly, in all embodiments, the irradiated crosslinked grommet comprises a crosslinked polymer, particularly a radiation-induced crosslinked polymer.
[0017] In some optional forms, the crosslinked polymer is prepared by a process that includes adding a crosslinker to the polymer mixture prior to the formation of the grommet. The crosslinker may be selected from one or more crosslinkers in the group of peroxide crosslinkers, silane crosslinkers, bis(maleimide) crosslinkers, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate. Combinations of the foregoing crosslinkers, and combinations of one or more of the foregoing crosslinkers with other crosslinkers, may also be used.
[0018] In yet another optional aspect, the crosslinked polymer is prepared by a process that includes exposing a precursor polymer material to radiation selected from e-beam radiation, gamma radiation, or a combination thereof. Generally, a preformed grommet comprising the precursor polymer material is exposed to the radiation, thereby forming a crosslinked grommet comprising a radiation-induced crosslinked polymer.
[0019] In yet another optional form, the crosslinked polymer comprises radiation-induced crosslinked nylon, preferably by radiation crosslinking of a precursor nylon having a relatively low oxygen atom content, such as, for example, nylon 6 / 12, nylon 11, nylon 12, or combinations thereof. Combinations of the aforementioned crosslinked nylons, and combinations of one or more of the aforementioned crosslinked nylons with other polymers, such as other crosslinked polymers, may also be used. Typically, a preformed grommet comprising the precursor nylon is exposed to radiation to induce crosslinking in the grommet prior to incorporation of the irradiated crosslinked grommet into a battery or battery seal assembly, but after formation of the grommet itself. Alternatively, the precursor nylon may be crosslinked by irradiation to form a radiation-induced crosslinked nylon prior to grommet formation.
[0020] In yet other optional forms, the precursor polymer material, or a preformed grommet comprising same, is irradiated with a radiation dose of at least 50 kGy, at least 100 kGy, at least 125 kGy, at least 150 kGy, at least 200 kGy, and / or at least 250 kGy, e.g., 300 kGy, 350 kGy, or more.
[0021] In yet another optional embodiment, the crosslinked polymer comprises a crosslinked polymer selected from one or more crosslinked polymers in the group: crosslinked low density polyethylene (LDPE), crosslinked high density polyethylene (HDPE), crosslinked atactic polypropylene (PP), crosslinked isotactic PP, crosslinked polyvinyl chloride, crosslinked polypropylene oxide, crosslinked polyvinyl acetate, crosslinked polybutadiene, crosslinked polystyrene, crosslinked polymethyl acrylate, crosslinked polymethyl methacrylate. Combinations of the foregoing crosslinked polymers, as well as combinations of one or more of the foregoing crosslinked polymers with other crosslinked polymers, may also be used.
[0022] In yet another optional aspect, the grommet includes a short boss or a long boss.
[0023] In yet other optional embodiments, the meshing interference between the grommet and the current collector is greater than 15%, greater than 17.5%, and / or greater than 19%, such as about 20%.
[0024] In yet other optional embodiments, the gel content of the crosslinked polymer is greater than 50%, greater than 70%, and / or greater than 90%. [Brief description of the drawings]
[0025] While the specification concludes with claims which particularly point out and distinctly claim the subject matter which is deemed to form part of the disclosure, the present invention will be better understood from the following description taken in conjunction with the accompanying drawings.
[0026] [Figure 1] 1 is a cross-sectional view of a seal assembly for a battery cell, the seal assembly including a bridging grommet.
[0027] [Diagram 2] 13 is a cross-sectional view of a further embodiment of a seal assembly including a bridging grommet;
[0028] [Figure 3A] 1 is a graph illustrating the percentage of the total number of AA battery cells with irradiated crosslinked grommets that show signs of leakage compared to comparative AA battery cells with non-crosslinked grommets versus exposure dose over a two week period.
[0029] [Figure 3B] 1 is a graph illustrating the percentage of the total number of AA battery cells with irradiated crosslinked grommets that show signs of leakage compared to comparative AA battery cells with non-crosslinked grommets versus exposure dose over an 8 week period.
[0030] [Figure 3C]1 is a graph illustrating the percentage of the total number of AA battery cells with irradiated crosslinked grommets that show signs of leakage compared to comparative AA battery cells with non-crosslinked grommets versus exposure dose over a 14-week period.
[0031] [Figure 4A] 1 is a graph of the molecular weight change of a precursor polymer material of a grommet, including a particular exemplary polymer, nylon 6 / 12, after exposure of the grommet to various levels of irradiation.
[0032] [Figure 4B] 1 is a graph of the molecular weight change of a precursor polymer material of a grommet, including a particular exemplary polymer, HDPE, after exposure of the grommet to various levels of irradiation.
[0033] [Diagram 5] FIG. 1 is a cross-sectional view of an exemplary battery cell having a jellyroll configuration. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0034] Electrochemical cells, or batteries, can be primary or secondary. Primary batteries are intended to be discharged (e.g., to empty) only once and then discarded. Primary batteries (or disposable batteries) are described, for example, in David Linden, Handbook of Batteries (4th ed., 2011), which is incorporated herein by reference. Secondary batteries (or rechargeable batteries) are intended to be charged and used repeatedly. Secondary batteries can be discharged and charged many times, for example, 50 or more times, 100 or more times, or more. Secondary batteries are described, for example, in David Linden, Handbook of Batteries (4th ed., 2011), which is also incorporated herein by reference. Thus, batteries can include a variety of electrochemical couples and electrolyte combinations. The description and examples provided herein apply to both primary and secondary batteries, including aqueous, non-aqueous, ionic liquid, and solid-state systems. Although consumer, single-use primary alkaline battery cells are the primary focus of the accompanying description, the following description may be equally applicable to any battery cell, including, but not limited to, rechargeable alkaline battery cells, such as rechargeable alkaline manganese (RAM) battery cells, lithium-ion battery cells, and any other type of battery cell that contains an electrolyte solution (whether aqueous or non-aqueous based).
[0035] Surprisingly and unexpectedly, seal assemblies comprising the bridged grommets described herein exhibit improved performance, as evidenced by reduced leakage of battery cells containing same. As previously mentioned, conventional grommets typically comprise flexible materials, and therefore, it is counterintuitive to use a stiffer material therefor (resulting from bridged bridging), as such materials would be expected to be more susceptible to crack and penetration formation. It should be understood that the term "grommet" is used interchangeably with the term "seal" herein.
[0036] Advantageously, the bridged grommet according to the present disclosure can be included in any type of electrochemical battery cell that includes an electrolyte. For example, the bridged grommet according to the present disclosure can be used in consumer electrochemical cells of any size and / or shape, including but not limited to AAAA cells, AAA cells, AA cells, B cells, C cells, D cells, 9V cells, etc., including but not limited to cylindrical, rectangular, or square shapes, or batteries having the aforementioned cross-sectional configurations. The disclosed bridged grommet is particularly advantageous when incorporated into alkaline electrochemical cells, particularly alkaline cells that include a seal assembly comprising the disclosed bridged grommet and a current collector disposed in the bore of the bridged grommet.
[0037] As used herein, the terms "crosslinked" and "crosslinking treatment" refer to a crosslinked polymer structure resulting from an intended crosslinking, a method for crosslinking a precursor polymer, and / or a method for crosslinking a preformed grommet by exposing the preformed grommet to a crosslinking treatment after grommet formation. As is known, grommet formation is typically performed using injection molding techniques. Typically, crosslinking of a non-crosslinked precursor polymer can be achieved using known techniques that promote crosslinking of the precursor polymer, such as by adding a crosslinking agent to the precursor polymer to initiate crosslinking and / or by exposing the precursor polymer to radiation. In one example, crosslinking can be achieved during grommet formation by adding a crosslinking agent to the precursor polymer to form a mixture and injection molding the mixture as the required temperature increase reacts the precursor polymer and crosslinking agent. Other techniques for crosslinking the precursor polymer before, during, or after molding can also be used, alone or in combination. Examples of cross-linking treatments after grommet formation include exposing a preformed grommet containing a precursor polymer material to radiation or exposing a preformed grommet containing a precursor polymer material to a chemical bath. Other techniques that promote cross-linking of preformed polymer components such as grommets may also be used. In all of these cases, the precursor polymer of the preformed grommet may further include a cross-linking agent to facilitate the intended cross-linking. The cross-linking treatment promotes cross-linking at both exposed polymer grommet surfaces and in the polymer bulk material beyond the exposed polymer surfaces (e.g., within the internal structure of the polymer grommet).
[0038] As used herein, the term "irradiation" refers to exposure to e-beam, gamma radiation, or a combination of the foregoing, at a dosage sufficient to induce crosslinking.
[0039] As used herein, the term "crosslinked grommet" refers to a grommet that includes a polymeric material that includes crosslinks between polymer chains, where the crosslinks may be formed by any crosslinking process, including, for example, irradiation, initiating / facilitating a chemical reaction that forms the crosslinks, or a combination thereof. The crosslinking process may be completed before, during, or after the formation of the grommet. When crosslinking is performed before or during the formation of the grommet, typically non-crosslinked precursor polymeric material is crosslinked before and / or during grommet formation, such that a crosslinked polymeric material is used to form the grommet. It is understood that, particularly with respect to crosslinking performed after grommet formation, the term "crosslinked grommet" refers to a grommet that has a different polymer structure than a grommet that includes a precursor polymeric material (that has not been subjected to an intended crosslinking process).
[0040] As used herein, the term "irradiated crosslinked grommet" refers to a grommet that includes a polymeric material that includes crosslinks between polymer chains, the crosslinks being created by exposing the grommet to irradiation after the grommet has been formed into its final shape. Typically, irradiating the preformed grommet occurs before the grommet is installed in a battery cell. Exposing a "preformed grommet" that includes a precursor polymeric material to a sufficient dose of irradiation creates crosslinks in the precursor polymeric material, thereby forming an irradiated crosslinked polymeric grommet that includes crosslinks within the internal structure of the polymeric grommet. Thus, it is understood that the term "irradiated crosslinked grommet" refers to a grommet that has a different polymeric structure than a grommet that includes a precursor polymeric material (that has not been subjected to an intended crosslinking process).
[0041] As used herein, the term "interference" refers to the interference between the current collector and the grommet, specifically the ratio of the outer diameter of the current collector minus the inner diameter of the grommet bore, i.e., the inner diameter of the grommet opening, to the inner diameter of the grommet opening. The outer diameter of the current collector is traditionally larger than the inner diameter of the grommet to provide an interference fit and thereby improve sealing properties, but in prior art battery cells, the interference is typically less than 15% to facilitate assembly of the battery cell.
[0042] As used herein, the term "gel" refers to a state of matter that is interconnected in aggregates that cannot be dissolved further in various solvents. A higher amount of gel indicates a higher number of cross-links between polymer chains. Such bonds advantageously prevent the material from dissolving in solvents, increase resistance to temperature fluctuations, and also increase the rigidity of the polymer material.
[0043] As used herein, the term "about" means + / - 10% of any recited value, or, in the alternative, + / - 5% of any recited value. As used herein, the term modifies any recited value, range of values, or end points of one or more ranges.
[0044] Irradiated grommets are created by exposing the fully formed grommets to electron beam radiation, gamma radiation, or a combination of the foregoing. To create irradiated grommets, the fully preformed set of grommets can be subjected to one or more irradiation treatments, for example, using an electron beam accelerator including a conveyor. Thus, the irradiation treatment can include passing the set of preformed grommets through a radiation zone to administer a radiation dose of typically about 25 kGy to about 50 kGy. When multiple irradiation treatments are performed on a set of preformed grommets to provide an integrated dose of radiation, it can be advantageous to vary the relative position of the grommets between treatments to ensure more uniform radiation exposure between the grommets. Typically, the energy of the beam is about 1 MeV to about 4.5 MeV, and the power of the accelerator is 25 kW to 200 kW. For example, a 1.5 MeV, 75 kW accelerator can be used. Wasik, IOTRON, and IBA all manufacture suitable e-beam accelerators.
[0045] In embodiments, a preformed grommet comprising a precursor polymer material may further include a crosslinking agent distributed or dispersed throughout the matrix of the precursor polymer material. The crosslinking agent may be embedded or otherwise dispersed throughout the preformed grommet matrix of the precursor polymer material. Molding of the precursor polymer material to form a grommet involves increasing the temperature so that reaction of the precursor polymer with the crosslinking agent, and thus crosslinking of the precursor polymer, may occur during grommet formation. In addition, irradiation of a preformed grommet with embedded crosslinking agent advantageously produces additional crosslinks between the polymer chains in the grommet (relative to the amount of crosslinks created solely by injection molding a mixture of the precursor polymer and the crosslinking agent, and relative to the amount of crosslinks created solely by irradiation) due to (additional) reaction of the polymer chains with the embedded crosslinking agent upon irradiation. The additional crosslinks created by reaction of the accelerator or crosslinking agent may further improve the mechanical properties of the irradiated crosslinked grommet.
[0046] In other embodiments, the grommet may be crosslinked prior to further irradiation processing. For example, a crosslinked grommet may be formed by fabricating a grommet including a precursor polymer material by injection molding of the precursor polymer material having a crosslinking agent embedded therein, as described above, optionally followed by further processing (e.g., heat treatment or immersion in a chemical bath) to initiate or cause additional reaction of any remaining embedded crosslinking agent within the precursor polymer material, thereby providing additional crosslinks between the polymer chains within the grommet. Subsequent irradiation of such a crosslinked grommet will produce additional crosslinks between the polymer chains within the grommet.
[0047] A number of crosslinking agents can be used. Crosslinking agents containing multiple reactive functional groups, such as vinyl groups, can react with multiple polymer chains to create crosslinks. Free radical initiator crosslinking agents, silane coupling agent crosslinking agents, and chain extender crosslinking agents can also be used. Suitable crosslinking agents for distribution or dispersion throughout the matrix of the precursor polymeric material described above include, but are not limited to, peroxides such as hydrogen peroxide, benzoyl peroxide, dilauryl peroxide, and dicumyl peroxide; silanes such as vinyltrimethoxylsilane, vinyltriethoxysilane, 3-(trimethoxysilylpropyl methacrylate, vinyltris(2-methoxyethoxy)silane, vinyltris(methylethylketoxime)silane, (3-aminopropyl)triethoxysilane, (3-aminopropyl)trimethoxysilane, (N-2-aminoethyl-3-aminopropyl)trimethoxysilane; N,N'-(1,2-phenylene)dimaleimide, N,N'-(1,3-phenylene)dimaleimide, N,N'-(1,4-phenylene)dimaleimide, N,N'-(1,5-phenylene)dimaleimide, N,N'-(1,6-phenylene)dimaleimide, N,N'-(1,7-phenylene)dimaleimide, N,N'-(1,8-phenylene)dimaleimide, N,N'-(1,9-phenylene)dimaleimide, N,N'-(1,10-phenylene)dimaleimide, N,N'-(1,2-phenylene)dimaleimide, N,N'-(1,3 ...4-phenylene)dimaleimide, N,N'-(1,5-phenylene)dimaleimide, N,N'-(1,6-phenylene)dimaleimide, N,N'-(1,7-phenylene)dimaleimide, N,N'-(1,8-phenylene)dimaleimide, N,N'-(1,9-phenylene)dimaleimide, N,N'-(1,10 Examples of crosslinking agents include bis(maleimide) compounds such as N'-(1,4-phenylene)dimaleimide 1,4-di(maleimide)butane, N,N'-(methylenebis(1,4-phenylene))-bis(maleimide), triallyl cyanurate, triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate. In addition, crosslinking agents available under the trade name NEXAMITE® (Nexam Chemical) may be used, including but not limited to NEXAMITE® A32 and NEXAMITE® A33 (for crosslinking nylon containing precursor polymeric materials), and NEXAMITE® A48 and NEXAMITE® A49 (for crosslinking polyethylene containing precursor polymeric materials). Of course, the aforementioned crosslinking agents are merely exemplary, and other crosslinking agents may be used.
[0048] When a crosslinking agent is used, it is typically added to the precursor polymeric material such that it is distributed or dispersed throughout the matrix of the precursor polymeric material prior to forming the grommet. Crosslinking may be initiated prior to, during, and / or after grommet formation, as discussed above. Crosslinking agents may be particularly effective in promoting more uniform formation of crosslinks throughout the matrix of the precursor polymeric material.
[0049] In one embodiment, a method of making an alkaline battery cell having a cross-linked grommet includes providing a pre-formed grommet including a precursor polymer material. The pre-formed grommet is exposed to a cross-linking treatment, such as radiation and / or a chemical cross-linking bath, to cross-link the precursor polymer material, thereby forming a cross-linked grommet. The cross-linked grommet may be incorporated into a battery cell, e.g., a primary battery cell or a secondary battery cell. A seal assembly may also be formed that includes the cross-linked grommet and a current collector disposed in a bore of the cross-linked grommet. The cross-linked grommet and / or the seal assembly that includes the same may then be disposed in a battery cell, e.g., a primary battery cell or a secondary battery cell, that includes an electrolyte.
[0050] In one embodiment, the method includes exposing the preformed grommet to radiation, such as electron beam (e-beam), gamma radiation, or a combination thereof, to form an irradiated crosslinked grommet. When e-beam radiation is used, radiation doses of at least 40 kGy, at least 50 kGy, at least 100 kGy, at least 125 kGy, at least 150 kGy, at least 200 kGy, and / or at least 250 kGy, such as 300 kGy, 350 kGy, 400 kGy, or even more, can be particularly useful for providing and / or maximizing chemical crosslinks in the polymeric material. For example, the e-beam radiation dose can be from about 40 kGy to less than 500 kGy, from about 50 kGy to about 450 kGy, and / or from 75 kGy to about 400 kGy. Radiation doses in the amount of about 250 kGy to about 400 kGy have been shown to be advantageous for crosslinking preformed grommets, particularly crosslinked grommets comprising thermoplastic polyolefins, including but not limited to polyethylenes such as ultra-high density polyethylene (UHDPE), low density polyethylene (LDPE), and high density polyethylene (HDPE), polypropylenes such as atactic polypropylene (PP) and isotactic PP, and polyvinyl chloride, having interdigitation interference of greater than 15%. E-beam radiation can be achieved, for example, by using an electron gun to generate and accelerate the primary beam and a magneto-optical system to focus and deflect the beam. Multiple passes with smaller radiation dose increments are typically used to achieve the desired dosage, for example, in increments of 10 kGy, 20 kGy, 25 kGy, 30 kGy, or 50 kGy. Higher increments can also be used, as long as the grommet structure is not overheated to the point of deformation. The energy of the electron beam can vary from 300 keV to 20 MeV, 1 MeV to 10 MeV, 3 MeV to 10 MeV, for example, a 4.5 MeV electron beam can be used.
[0051] The strength properties of the crosslinked grommet may be further improved by annealing the crosslinked grommet after completion of the crosslinking and / or irradiation process, for example by applying heat. Annealing is performed above 25°C, preferably between 40°C and 135°C, but below the melting point of the crosslinked polymer. Generally, annealing is accomplished by treatment in a bath for a period of one hour or more, typically for a period of at least about four hours, and then the crosslinked grommet is cooled to room temperature. Without intending to be bound by theory, it is believed that the annealing process increases the mobility of the chains relative to each other, which facilitates the completion of the crosslinking chemical reaction with free radicals in the grommet polymer matrix that did not complete the crosslinking reaction, for example, after exposure to radiation, chemical soak baths, and / or during grommet formation. Thus, additional bonds between the polymer chains are formed and the tensile properties of the polymeric material may be further improved as a result of annealing.
[0052] In any embodiment, the current collector (which may be a nail) may comprise a conductive metal, such as a brass alloy or a bronze alloy (including silicon bronze). A brass alloy having a copper content of greater than about 50% by weight, e.g., 60% or 70% by weight, and a zinc content of greater than 20% by weight, e.g., 30% or 40% by weight, may be used.
[0053] Generally, thermoplastic polymers can be used to form the crosslinked grommet according to the present disclosure. For example, nylons such as nylon 6, nylon 6 / 6, nylon 4 / 6, nylon 3, nylon 12, nylon 11, and nylon 6 / 12, nylon 10 / 20, nylon 10 / 12, nylon 6 / 10, nylon 4 / 12, and nylon 4 / 10, as well as polyethylenes such as ultra-high density polyethylene (UHDPE), low density polyethylene (LDPE), and high density polyethylene (HDPE), polypropylenes such as atactic polypropylene (PP) and isotactic PP, polyvinyl chloride, polypropylene oxide, polyvinyl acetate, polybutadiene, polystyrene, polymethyl acrylate, polymethyl methacrylate, or combinations thereof may be used. The crosslinked polymeric material of the seal disclosed herein is preferably a non-ionic crosslinked polymer.
[0054] Since nylons are polyamides, all nylons exhibit hydrogen bonding (C=O...HN) between adjacent polymer chains. In general, an increase in hydrogen bonding between polymer chains imparts improved mechanical properties to polymeric materials without making the material overly stiff. For nylons specifically, the amount of hydrogen bonding is expected to correspond to the density of amide groups in the polymer, i.e., considering two nylon polymers, the one with more amide groups is expected to exhibit more hydrogen bonding. For nylons, the density of amide groups depends on the chain length of the precursor molecule. By increasing the chain length of the precursor, the number of C-C bonds between amide groups on the polymer chain increases, and the density of amide groups in the polymer decreases. Thus, nylons made from short chain precursors are expected to have a higher density of amide groups and therefore exhibit a higher degree of hydrogen bonding and be more suitable for grommets for battery cells than nylons made from longer chain precursors. Thus, a group of polymers suitable for fabricating grommets having favorable mechanical strength includes nylon 6, nylon 6 / 6, and nylon 4 / 6, all of which would be expected to exhibit a higher degree of hydrogen bonding, and therefore superior mechanical properties, compared to nylons prepared from longer chain precursors such as nylon 12, nylon 11, and nylon 6 / 12. Surprisingly, this is not the case.
[0055] One way to compare the structures of various nylons is to look at the number of oxygen atoms ("%O") as a percentage of non-hydrogen atoms in each polymer. For example, in nylon 6, the repeating unit is C5H 10 C(=O)NH, so %O is 1 / 8=12.5%. In the case of nylon 12, the repeating unit is C 11 H 22C(=O)NH, with the corresponding %O being 1 / 14=7.1%. In general, polymers with a higher %O have a higher density of amide groups and therefore are expected to exhibit a higher degree of hydrogen bonding and therefore superior mechanical properties compared to polymers with lower %O. Thus, as discussed above, shorter chain nylons with a higher relative amount of hydrogen bonds are expected to have superior mechanical properties. Surprisingly, however, crosslinked grommets comprising longer chain, lower %O nylons such as nylon 12, nylon 11, or nylon 6 / 12 perform as well as or even better than grommets made with shorter chain nylons such as nylon 6 / 6. For example, surprisingly and unexpectedly, the mechanical properties of irradiated crosslinked nylon 6 / 12 (%O=9.1%) are nearly equal to those of non-irradiated non-crosslinked nylon 6 / 6 (%O=12.5%), which is generally believed in the industry to provide the most effective grommet, but is very expensive. Moreover, surprisingly and unexpectedly, irradiated crosslinked grommets comprising nylon 6 / 12 exhibit superior leak protection when compared to similarly irradiated crosslinked grommets comprising nylon 6 / 6. Thus, crosslinked nylon 6 / 12, which has superior leakage performance to crosslinked nylon 6 / 6, is a particularly useful material for crosslinked grommets for battery cells.
[0056] On the other hand, polymers such as nylon 4-6, nylon 6, nylon 6-6, and nylon 3, which have %O values greater than 12%, have excellent hydrogen bonding and sufficient tensile properties in dry conditions, but surprisingly, these polymers are prone to increased degradation in the presence of water, resulting in their tensile properties decreasing in battery cells containing aqueous electrolytes. In particular, nylon 6-6 is relatively stable in electrolytes containing high alkali hydroxide concentrations of greater than 30 weight percent (wt.%) based on the weight of the total electrolyte in the battery cell, but is prone to decomposition, such that cracks can form more easily in the grommet at relatively low alkali hydroxide concentrations of less than 30 wt.%, less than 25 wt.%, and less than 20 wt.%. The alkali hydroxide can be, for example, potassium hydroxide, cesium hydroxide, or any combination thereof, but is typically potassium hydroxide. Without intending to be bound by theory, the greater the number of oxygen atoms in nylon or other polymeric materials, the higher the saturated water content and the greater the rate of hydrolysis over time, and therefore the greater the material failure. As a result, nylons with a low percentage of oxygen atoms in their structure, e.g., nylon 6-12, nylon 12, nylon 11, or even polyolefins such as HDPE or LDPE with 0% oxygen atoms in their structure, are surprisingly preferred, even though the tensile properties of such plastics are reduced by the presence of relatively few hydrogen bonds between polymer chains (e.g., between amide groups -C=O···HN- of adjacent polymer chains). For example, without intending to be bound by theory, the inventors have found that grommets made of nylon react (through hydrolysis) with any water present in the electrolyte, which causes the nylon to degrade and decompose, ultimately resulting in cracking of the material allowing electrolyte creep. Crosslinking of grommets containing nylons with longer chains and lower %O, such as nylon 12, nylon 11, or nylon 6 / 12, in particular, advantageously increases the resistance of the crosslinked grommet to hydrolysis.
[0057] Additionally, and again without intending to be bound by theory, the inventors have found that grommets made of polyolefins such as polyethylene and polypropylene, while less susceptible to hydrolysis, are also prone to cracking, especially under pressure. Such cracking is problematic for any battery cell seal or grommet, including but not limited to those where the current collector is provided in the form of a nail. For example, cracks and penetrations that form in the grommet due to such structural degradation can ultimately cause seal failure and / or creep of the electrolyte solution between the nail and the grommet. Crosslinking of grommets that include polyolefins such as polyethylene and polypropylene, in particular, advantageously increases the material strength of the crosslinked grommet such that fewer cracks form in the crosslinked grommet, which is particularly surprising considering that the increased stiffness of the material resulting from crosslinking of the precursor polymeric materials would be expected to make the crosslinked material more susceptible to crack and penetration.
[0058] Thus, polymers such as polyethylenes such as UHDPE, HDPE, and LDPE, polypropylenes such as atactic PP and isotactic PP, polyvinyl chloride, polybutadiene, polystyrene, nylon 10 / 20, nylon 12, nylon 11, nylon 10 / 12, nylon 6 / 12, nylon 6 / 10, nylon 4 / 12, and nylon 4 / 10, all containing less than 12% O, are expected to provide improved properties upon crosslinking and / or increased resistance to hydrolytic degradation, which is surprising and unexpected, especially given our findings that nylons are generally susceptible to hydrolysis and other thermoplastic polymers such as polyolefins are susceptible to material failure. Polymers with less than 12% O, less than 10% O, less than 8% O, and / or less than 5% O are particularly useful for crosslinking grommets for battery cells.
[0059] Relative to the current state of the art, it has been found that increasing the meshing interference between the grommet and the current collector surprisingly and advantageously improves grommet performance, as evidenced by reduced leakage, despite increased strain of the stiffer material. The meshing interference may be greater than 15%, greater than 17.5%, and / or greater than 19%, for example, about 20% or more. Such increased meshing interference is particularly advantageous for grommets comprising crosslinked polyethylenes, such as UHDPE, HDPE, and LDPE, crosslinked polypropylenes, such as atactic PP and isotactic PP, and crosslinked nylons, such as nylon 6-12d, nylon 12, and nylon 11.
[0060] Furthermore, by increasing the level of crosslinking, for example by using a greater amount of irradiation, additional crosslinks are formed between adjacent polymer chains. These additional crosslinks can be measured and detected as an increase in molecular weight relative to the molecular weight of the polymer precursor material. During testing, after exposing grommets containing precursor polymers including nylon 6-12 to 200 kGy of irradiation, a greater than 10-fold increase in molecular weight was demonstrated using size exclusion chromatography, thereby confirming the formation of crosslinks between polymer chains. In general, crosslinked polymers having higher molecular weights surprisingly demonstrate better tensile properties and less creep, allowing electrochemical battery cells to better withstand the temperature fluctuations to which they are frequently exposed during storage and shipping, providing a grommet / seal that surprisingly performs better in electrochemical battery cells.
[0061] In another example, gels formed in grommets comprising precursor polymeric materials including nylon 6-12 as radiation doses increased above 200 kGy. Advantageous grommet performance was demonstrated when the gel content of the crosslinked polymer was greater than 50%, greater than 70%, and / or greater than 90%.
[0062] 1, there is illustrated one embodiment of an alkaline battery cell 10 including an exemplary seal assembly 15 according to the present disclosure. The seal assembly 15 includes a current collector or nail 30 and a bridging grommet or seal 28.
[0063] The battery cell 10 includes a first cover 12 and a second cover 14, which correspond to the negative and positive battery terminals, respectively, with a housing 16 generally disposed therebetween. To separate the anode 18 from the cathode 20, the battery cell 10 includes a separator 22. After the components of the battery cell 10 are disposed within the housing 16, to close the end 24, the first cover 12 is received within a groove 26 formed in an outer peripheral wall 52 of a bridging grommet 28, and a side wall 29 of the housing 16 is crimped around the periphery of the bridging grommet 28, thereby enclosing the bridging grommet 28 within the housing 16. In some examples, the bridging grommet 28 is spaced apart from the cathode 20 to allow the cathode 20 to expand. In some examples, the bridging grommet 28 is spaced apart from the anode 18 to allow the anode 18 to expand. The bridging grommet 28 is annular in the illustrated example in order to cover the end of the generally cylindrical side wall 29 .
[0064] To couple the anode current collector 30 to the first cover 12 that provides the negative terminal for the assembled battery cell 10, in this example, the bridging grommet 28 includes a first opening or bore 32 having a wider portion 34 that defines a head gap or space 36 in which an end or head 38 of the anode current collector 30 is positioned and electrically coupled to the first cover 12. This space 36 may have a chamfered or angled configuration to accommodate the head 38. In this example, the body 40 of the anode current collector 30 extends through the first opening 32 into the anode 18. The first opening 32 may be surrounded by a boss 50, which in the illustrated example is a short boss. The first opening 32 has an inner diameter that generally corresponds to the outer diameter of the current collector / nail 30. The outer diameter of the current collector 30 is typically larger to provide an interference fit between these components of the seal assembly 15, and in some preferred embodiments, the outer diameter of the current collector 30 is at least 15% larger than the inner diameter of the first opening 32, as described above.
[0065] As used herein, a short boss refers to a boss 50 that extends either below the generally flat annular portion or shelf 35 of the bridging grommet 28 or above the shelf 35, but not both. In other examples, described further below, the boss 50 may be a long boss. As used herein, a long boss refers to a boss 50 that extends both above and below the shelf 35 of the bridging grommet 28.
[0066] An electrolyte solution is contained within the housing 16, and the electrolyte solution facilitates the chemical reaction between the anode 18 and the cathode 20. The electrolyte may be an alkali hydroxide, such as potassium hydroxide, cesium hydroxide, or any combination thereof, but is typically potassium hydroxide.
[0067] To further reduce electrolyte creep, in additional embodiments, the above-mentioned bridging grommet may be implemented in a long boss design and further combined with a sealant trap, as shown in FIG. 2 and as disclosed, for example, in U.S. Patent Publication No. 2021 / 0367297(A1), the entirety of which is incorporated herein by reference. As shown in FIG. 2, the seal assembly 100 may include a bridging grommet 128 having an opening or bore 150. When assembled, a top portion 153 of the bridging grommet 128 is adjacent to a cover that provides the negative terminal of the battery cell, and a bottom portion 155 of the bridging grommet 128 is disposed closer to the anode, cathode, and electrolyte of the battery cell. The current collector or nail 130 has a nail head 138 and a body or stem extending from the nail head 138.
[0068] When assembled, the stem 140 extends through an opening 150 in the bridging grommet 128 from the top 153 through the bottom 155, with the nail head 138 seated in a head space near the top 153. When assembled, the stem 140 and the bridging grommet 128 form a first interference fit 152 and a second interference fit 157. Each of the first interference fit 152 and the second interference fit 157 may have a meshing interference of more than 15%, more than 17.5%, and / or more than 19%, for example, about 20%. When assembled, a trapping gap 160 is formed radially and longitudinally between the stem 140 and the bore 150 and between the first interference fit 152 and the second interference fit 157. The trapping gap 160 defines a trap 160 for the sealant 170. The sealant 170 is disposed around the stem 140 and is at least partially located within the trap 160 to provide an additional sealing surface that cooperates with the first interference fit portion 152 and the second interference fit portion 157 to form an enhanced seal that reduces or prevents electrolyte from escaping the battery cell.
[0069] The stem 140 of the nail 130 includes a first portion 172 having a first stem diameter and a second portion 174 having a second stem diameter. The second stem diameter is smaller than the first stem diameter. As shown, the first portion 172 and the second portion 174 of the stem 140 are joined by a chamfer 176, however, a more "abrupt" step transition between the first portion 172 and the second portion 174 can also be used, provided that the second portion 174 has a smaller diameter than the first portion 172, as previously described. The first portion 172 of the stem 140 has an outer diameter that is larger than the inner diameter of the bore 150, as previously described.
[0070] The trap 160 is formed between the bore 150 and the second portion 174 of the stem 140. The trap 160 is radially bounded on an inner side by an outer surface of the second portion 174 and on an outer side by an inner surface of the bore 150. The trap 160 in the illustrated example defines an annular shaped space.
[0071] An inner annular ring 180 protrudes from an inner surface of the bore 150. The inner annular ring 180 forms a first interference fit 152 with the second portion 174 of the stem 140 when the stem 140 is fully inserted into the bridging grommet 128 because the outer diameter of the second stem 174 is larger than the inner diameter of the annular ring 180, as described above. Optionally, a lower bore 181 having a wider diameter than the inner annular ring 180 can be included that opens to the internal components of the battery cell.
[0072] The trap 160 is located longitudinally along the stem 140 and above the inner annular ring 180. In the example shown in Figure 2, the trap 160 is longitudinally bounded by the inner annular ring 180 and the chamfer 176 when the stem 140 is fully inserted into the bridging grommet 128. Thus, the structural arrangement of the stem 140 within the bore 150 is purposefully positioned to provide a void that is the trap 160 for the sealant 170.
[0073] 5, in another embodiment, the anode 518 and cathode 520 of an electrochemical battery cell 500, which may be a primary or secondary cell, are configured in a so-called "jelly roll" configuration. One example of a jelly roll configuration is described and illustrated in U.S. Patent No. 11,081,721, which is incorporated herein by reference in its entirety. The electrochemical battery cell 500 includes an anode 518 in electrical contact with a negative lead 594, a cathode 520 in electrical contact with a positive lead 592, a separator 522, and an electrolyte (not shown). The anode 518 and cathode 520, with the separator 522 disposed therebetween, may be rolled to form a jelly roll assembly. The anode 518, cathode 520, separator 522, and electrolyte are contained within a housing 516. The cell 500 further includes a first cover 594 and an annular insulating bridging grommet 528 disposed proximate to the first cover 594. The cell 500 may include a safety vent 530. EXAMPLES
[0074] The following examples further illustrate the advantages of battery cells including bridged grommets as disclosed herein.
[0075] Example A 3A-3C are graphs showing test data for AA battery cells containing irradiated crosslinked grommets containing crosslinked nylon 6 / 6 (and exposed to different doses of e-beam radiation) compared to otherwise identical comparative AA battery cells containing non-crosslinked nylon 6 / 6 grommets (not exposed to e-beam radiation). The battery cells were inspected after 2, 8, and 14 weeks, respectively. The x-axis in the graphs represents the radiation dose (kGy) and the y-axis in the graphs represents the total number of cells showing signs of leakage as a percentage of the total cells under test. In general, as shown in FIGS. 3A-3C, as the radiation dose increased, the percentage of cells showing signs of leakage significantly and surprisingly decreased. Without being bound by theory, it is believed that the improved leakage rate is due to increased crosslinking in the polymer grommets due to the exposure to higher radiation doses. The grommets of the test cells had a short boss design.
[0076] Example B Battery cells containing crosslinked grommets (and exposed to different doses of e-beam radiation) were subjected to leakage testing and compared to otherwise identical control battery cells containing non-crosslinked grommets. The battery cells had a KOH electrolyte solution containing approximately 25% KOH by weight. Cells were randomly taken from a control group (non-irradiated grommets) and an irradiated group (containing crosslinked and irradiated grommets). The irradiated group contained crosslinked grommets containing nylon 6 / 12 subjected to 200 kGy. The cells were then observed for evidence of leakage using a digital microscope at weekly intervals while held at elevated temperature conditions above 50°C intended to exacerbate defects that may cause leakage under normal battery storage conditions over a 12-year period of storage. The control cells with seals containing non-irradiated nylon 6 / 12 showed 7 leaking cells out of 30 after 8 weeks, while the irradiated cells with seals containing irradiated nylon 6 / 12 showed zero leaking cells out of 30 after 8 weeks. The grommets in the test cells had a short boss design.
[0077] Example C In a second example, battery cells containing short boss grommets were tested in a temperature shock test where the temperature was cycled between a relatively high temperature approaching 60°C and a relatively low temperature below -25°C to exacerbate any defects that may cause leakage under normal battery storage conditions over a 12 year storage period, and a high temperature and humidity test (approaching 60°C and 85% relative humidity). The material used was nylon 6 / 6. The seals of the control cells were not irradiated, and the seals of the irradiated cells received a radiation dose of up to 125 kGy. After 8 weeks, the irradiated cells showed a 65% reduction in leakage in the temperature shock test (92% of the control cells leaked while only 32% of the irradiated cells leaked) and a 33% reduction in leakage in the temperature and humidity test (12% of the control cells leaked while only 8% of the irradiated cells leaked).
[0078] Example DAdditional battery cells were assembled to further demonstrate the advantageous performance of the crosslinked grommets disclosed herein. Specifically, battery cells (Groups B, C, D, E, F, G, H, I, and J) containing crosslinked grommets comprising nylon 6 / 12 ("N6 / 12") or HDPE, current collectors with different outer diameters to generate various meshing interferences, and exposed to different doses of e-beam radiation were subjected to leakage testing and compared to an otherwise identical control battery cell (Group A) containing a non-crosslinked grommet. The battery cells had a KOH electrolyte solution containing about 25% KOH by weight. The control Group A grommets were not irradiated, while Groups B-J according to the present disclosure were irradiated at the doses shown in Table 1 below. The cells were subjected to high temperature and humidity testing (approaching 60°C and 85% relative humidity) to exacerbate defects that may cause leakage under normal battery storage conditions over a 12-year storage period, and observed for evidence of leakage at weekly intervals using a digital microscope with a 2500X lens (MXG-2500REZ lens, Hirox Co. Ltd., Japan). Control cells with a long boss confined sealant design (as described herein) containing non-irradiated nylon 6 / 12 showed 6 leaking cells out of 30 after 8 weeks, while cells containing irradiated grommets with a long boss design containing irradiated nylon 6 / 12 and irradiated HDPE showed surprisingly little leakage, especially at higher levels of radiation. Specifically, cells in groups B, C, and D had a long boss design without a trapped sealant, cells in groups E, F, and G had a long boss trapped sealant design, and cells in groups H, I, and J had a long boss design without a trapped sealant. Surprisingly, the leakage performance of the cells containing irradiated HDPE (groups C, D, H, I, and J) was improved relative to the control group A, which contained a long boss grommet containing non-irradiated nylon 6 / 12, especially at radiation doses above 250 kGy, which is particularly surprising and advantageous because these cells do not contain a trapped sealant that can provide an additional sealing surface.As shown in Table 1, surprisingly improved leakage results were observed for cells containing cross-linked nylon 6 / 12 and irradiated cross-linked HDPE irradiated with radiation doses above 200 kGy when the meshing interference was increased relative to control Group A. [Table 1]
[0079] Example E The crosslinked samples, including irradiated crosslinked HDPE and irradiated crosslinked nylon 12, were analyzed to determine gel content.
[0080] Specifically, a 0.5 g sample of the irradiated cross-linked HDPE material was weighed and placed into a jar. 100 mL of xylene was added, the jar was capped, and suspended in a 110°C oil bath for 24 hours. The sample was cooled, dried under vacuum, and weighed. The cross-linked HDPE sample was determined to contain approximately 97% gel (i.e., approximately 97% of the mass did not dissolve under these conditions). Xylene was chosen as the solvent because non-cross-linked HDPE is almost completely soluble in xylene at such high temperatures.
[0081] Similarly, a 0.5 g sample of irradiated crosslinked nylon 12 material was weighed and placed in a jar. 100 mL of 1,1,1,3,3,3-hexafluoro-2-propanol (HFIP) was added and the sample was immersed in HFIP for 24 hours. The sample was dried under vacuum and weighed. The crosslinked nylon 12 sample was determined to contain approximately 94% gel (i.e., approximately 94% of the mass did not dissolve under these conditions). HFIP was chosen as the solvent because non-crosslinked nylon 12 is nearly completely soluble in HFIP under these conditions.
[0082] Although some improvement in the tensile strength of the irradiated seals was expected, the magnitude of the improvement in leakage reduction was surprising and unexpected, particularly due to the increased stiffness of the seal material.
[0083] The foregoing results demonstrate that the disclosed seal assembly advantageously reduces electrolyte creep between the grommet and the nail, thereby extending the service life of the seal assembly for battery cells, particularly alkaline battery cells.
[0084] The dimensions and values disclosed herein are not to be understood as being strictly limited to the exact numerical values recited. Instead, unless otherwise specified, each such dimension is intended to mean both the recited value and a functionally equivalent range surrounding that value, to encompass conventional manufacturing tolerances.
[0085] All documents cited herein, including any cross-referenced patents or applications, are incorporated herein by reference in their entirety unless expressly excluded or otherwise limited. The citation of any document is not an admission that it is prior art to any invention disclosed or claimed herein, or that it alone, or in combination with any one or more other references, teaches, suggests, or discloses any such invention. Furthermore, in the event that any meaning or definition of a term in this document conflicts with any meaning or definition of the same term in a document incorporated by reference, the meaning or definition assigned to that term in this document shall control.
[0086] While particular embodiments of the present invention have been illustrated and described, it would be obvious to those skilled in the art that various other changes and modifications can be made without departing from the spirit and scope of the invention. It is therefore intended in the appended claims to cover all such changes and modifications that are within the scope of the invention.
Claims
1. 1. A seal assembly for a battery cell, comprising: a cross-linked grommet having an opening and comprising a cross-linked polymer; a current collector disposed within the opening and having a head and a stem extending from the head, the stem and the bridging grommet forming an interference fit with the opening.
2. 1. A seal assembly for a battery cell, comprising: an irradiated crosslinked grommet having an opening and comprising a radiation-induced crosslinked polymer; a current collector disposed within the opening and having a head and a stem extending from the head, the stem and the irradiated bridging grommet forming an interference fit with the opening.
3. The seal assembly of claim 1 or 2, wherein the current collector comprises a brass alloy or a bronze alloy.
4. The seal assembly of claim 1 or 2, wherein the cross-linked polymer comprises radiation-induced cross-linked nylon.
5. 5. The seal assembly of claim 4, wherein the radiation induced crosslinked nylon comprises one or more radiation induced crosslinked nylons selected from crosslinked nylon 10 / 20, radiation induced crosslinked nylon 12, radiation induced crosslinked nylon 11, radiation induced crosslinked nylon 10 / 12, radiation induced crosslinked nylon 6 / 12, radiation induced crosslinked nylon 6 / 10, radiation induced crosslinked nylon 4 / 12, and radiation induced crosslinked nylon 4 / 10.
6. 4. The seal assembly of claim 1, wherein the crosslinked polymer or the radiation-induced crosslinked polymer comprises one or more crosslinked polymers selected from crosslinked nylon 6, crosslinked nylon 6 / 6, crosslinked nylon 4 / 6, crosslinked nylon 3, crosslinked nylon 12, crosslinked nylon 11, crosslinked nylon 6 / 12, crosslinked nylon 10 / 20, crosslinked nylon 10 / 12, crosslinked nylon 6 / 10, crosslinked nylon 4 / 12, crosslinked nylon 4 / 10, crosslinked ultra high density polyethylene (UHDPE), crosslinked low density polyethylene (LDPE), crosslinked high density polyethylene (HDPE), crosslinked atactic polypropylene (PP), crosslinked isotactic PP, crosslinked polyvinyl chloride, crosslinked polypropylene oxide, crosslinked polyvinyl acetate, crosslinked polybutadiene, crosslinked polystyrene, crosslinked polymethyl acrylate, and crosslinked polymethyl methacrylate.
7. 4. The seal assembly of claim 1, wherein the crosslinked polymer or the radiation-induced crosslinked polymer comprises one or more crosslinked polymers selected from crosslinked HDPE, crosslinked LDPE, crosslinked atactic PP, crosslinked isotactic PP, crosslinked polyvinyl chloride, crosslinked polybutadiene, crosslinked polystyrene, crosslinked nylon 12, crosslinked nylon 11, and crosslinked nylon 6 / 12.
8. 8. The seal assembly of claim 1, wherein the radiation-induced crosslinked polymer is prepared by a process comprising exposing a preformed grommet comprising a precursor polymer material to one or more types of radiation selected from electron beam radiation and gamma ray radiation.
9. 9. The seal assembly of claim 8, wherein the radiation dose is at least 40 kGy, at least 50 kGy, at least 100 kGy, at least 125 kGy, at least 150 kGy, at least 200 kGy, and / or at least 250 kGy, e.g., 300 kGy, 350 kGy, or 400 kGy.
10. The seal assembly of any one of claims 1 to 3, wherein the cross-linked polymer is prepared by a process comprising reacting a cross-linking agent with a precursor polymer material.
11. The seal assembly of any one of claims 1 to 10, wherein the meshing interference between the bridging grommet and the current collector is greater than 15%, greater than 17.5%, and / or greater than 19%, for example, about 20%.
12. The seal assembly of any one of claims 1 to 11, wherein the cross-linked polymer has a gel content of greater than 50%, greater than 70%, and / or greater than 90%.
13. A battery cell, a housing including a first cover at a first housing end and a second cover at a second housing end, and an anode and a cathode disposed within the housing; a seal assembly adjacent to the first cover, the seal assembly including a current collector having a head and a stem extending from the head, and a cross-linked grommet having an opening and including a cross-linked polymer, the stem extending through the opening and forming an interference fit with the grommet.
14. 14. The battery cell of claim 13, wherein the crosslinked grommet is an irradiated crosslinked grommet and the crosslinked polymer comprises radiation induced crosslinked nylon.
15. The battery cell of claim 13 or 14, wherein the bridging grommet includes a short boss or a long boss.
16. The battery cell of any one of claims 13 to 15, further comprising an alkaline electrolyte.
17. 17. The battery cell of claim 13, wherein the meshing interference between the bridging grommet and the current collector is greater than 15%, greater than 17.5%, and / or greater than 19%, for example, about 20%.
18. The battery cell of any one of claims 13 to 16, wherein the cross-linked polymer has a gel content of greater than 50%, greater than 70%, and / or greater than 90%.
19. 1. A method of manufacturing a battery cell having a bridged grommet, the method comprising: forming a grommet comprising a precursor polymer material, thereby forming a preformed grommet; exposing the pre-formed grommet comprising the precursor polymer material to a cross-linking process, thereby forming a cross-linked grommet; and incorporating the bridging grommet into a battery cell.
20. 20. The method of claim 19, wherein the cross-linking process comprises exposing the grommet to radiation, thereby creating an irradiated cross-linked grommet.
21. 21. The method of claim 20, wherein the radiation comprises one or more radiation types selected from electron beam radiation and gamma ray radiation.
22. 22. The method of claim 21 , wherein the radiation is electron beam radiation and the radiation dose of the electron beam radiation reaches at least 40 kGy, at least 50 kGy, at least 100 kGy, at least 125 kGy, at least 150 kGy, at least 200 kGy, and / or at least 250 kGy, e.g., 300 kGy, 350 kGy, or 400 kGy.
23. The seal assembly of any one of claims 1 to 12, the battery cell of any one of claims 13 to 18, and the method of any one of claims 19 to 22, wherein the crosslinked grommet and / or the preformed grommet comprises a polymer having an oxygen atom content as a non-hydrogen atom content of less than 12%, less than 10%, less than 8%, and / or less than 5%.
24. The method of claim 19 , wherein the precursor polymer material further comprises one or more crosslinking agents.
25. 25. The method of claim 24, wherein the chemical crosslinker comprises one or more crosslinkers selected from peroxide crosslinkers, silane crosslinkers, bis(maleimide) crosslinkers, triallyl cyanurate, triallyl isocyanurate, trimethylolpropane triacrylate, and trimethylolpropane trimethacrylate.
26. 1. A bridging grommet for a battery cell, the bridging grommet comprising:
1. A grommet comprising an annular polymeric disk comprising a polymeric material and having a peripheral wall and a central boss surrounding a central opening for receiving a current collector, the polymeric material of the annular polymeric disk being crosslinked.
27. 27. The grommet of claim 26, wherein the polymeric material is crosslinked by exposure to radiation.
28. 25. The grommet of claim 24, wherein the radiation comprises electron beam radiation and the radiation dose is at least 40 kGy, at least 50 kGy, at least 100 kGy, at least 125 kGy, at least 150 kGy, at least 200 kGy, and / or at least 250 kGy, e.g., 300 kGy, 350 kGy, or 400 kGy.
29. 29. The grommet of any one of claims 26 to 28, wherein the polymeric material of the annular polymer disc comprises one or more crosslinked polymers selected from the group consisting of crosslinked nylon 6, crosslinked nylon 6 / 6, crosslinked nylon 4 / 6, crosslinked nylon 3, crosslinked nylon 12, crosslinked nylon 11, crosslinked nylon 6 / 12, crosslinked nylon 10 / 20, crosslinked nylon 10 / 12, crosslinked nylon 6 / 10, crosslinked nylon 4 / 12, crosslinked nylon 4 / 10, crosslinked ultra high density polyethylene (UHDPE), crosslinked low density polyethylene (LDPE), crosslinked high density polyethylene (HDPE), crosslinked atactic polypropylene (PP), crosslinked isotactic PP, crosslinked polyvinyl chloride, crosslinked polypropylene oxide, crosslinked polyvinyl acetate, crosslinked polybutadiene, crosslinked polystyrene, crosslinked polymethyl acrylate, and crosslinked polymethyl methacrylate.
30. The grommet of any one of claims 26 to 29, wherein the crosslinked polymeric material has a gel content of greater than 50%, greater than 70%, and / or greater than 90%.
31. 1. An alkaline battery cell, comprising: a housing including a first cover at a first housing end and a second cover at a second housing end, an anode, an alkaline electrolyte, and a cathode disposed within the housing; an irradiated cross-linked grommet comprising a radiation-induced cross-linked polymer adjacent to the first cover.
32. 32. The seal assembly, battery, method of manufacturing a battery cell, grommet, or alkaline battery cell of any one of claims 1 to 31, wherein the crosslinked grommet or the irradiated crosslinked grommet comprises a non-ionic polymer.